Respuesta :

[3 6 3]

( 3 3. 3]

THIS ANSWER IS CORRECT

Solution:

[tex]\sf \left[\begin{array}{ccc}3&6&3\\3&-3&-3\end{array}\right][/tex]

Explanation:

[tex]\sf \left[\begin{array}{ccc}3&6&3\\-3&3&3\\\end{array}\right][/tex]

The rule for a reflection over the x -axis is (x,y) → (x,−y)

===============================================================

or multiply the matrix with:      [tex]\left[\begin{array}{ccc}1&0\\0&-1\end{array}\right][/tex]

[tex]\dashrightarrow \ \sf \begin{pmatrix}1\cdot \:3+0\cdot \left(-3\right)&1\cdot \:6+0\cdot \:3&1\cdot \:3+0\cdot \:3\\ 0\cdot \:3+\left(-1\right)\left(-3\right)&0\cdot \:6+\left(-1\right)\cdot \:3&0\cdot \:3+\left(-1\right)\cdot \:3\end{pmatrix}[/tex]

Final answer:

[tex]\sf \left[\begin{array}{ccc}3&6&3\\3&-3&-3\end{array}\right][/tex]